Analisis Penentuan Prioritas Pengembangan Sektor Perekonomian di Kabupaten Sukoharjo - Irianto, Heru (Universitas Sebelas Maret, 2004)
The research aims to determine priority economic sector to develop at Sukoharjo Regency. Based method used in research is descriptive with using time series data for 1998 to 2002 about economic sector on GRDP (Gross of Regional Domestic Product) of Sukoharjo Regency. Analysis method use combination Location Quotient (LQ) and Shift share (SS) Model. Its result, the first sector to develop are Contruction, and the second sector are Mining and quaning, Electricity, Gas and Water supply sector, Trade, hotel and restaurant sector, Transport and communication sector, Agriculture sector and Services sector. Finally sector to develop are manufacturing industry and financial, ownership and business service sector.